Environmental Protection and Economic Offenses - Advantages and Disadvantages - Lukić, Natalija (Glasnik Advokatske komore Vojvodine, 2025)
The emerging forms of criminality to the detriment of the environment are diverse, and due to the huge consequences that affect the environment as well as the health and life of people, in the reports of numerous international organizations, they are classified at the very top of dangerous and growing criminal activities. The inadequate application of criminal law in combating environmental crime can be added as a reason, and in connection with that, the replacement of that branch of law in practice with other legal mechanisms. The subject of the paper is the analysis of economic offenses as special offenses of the domestic legal system and their advantages and disadvantages in environmental protection. The paper first points out the basic characteristics of economic crimes. The author analyzes the concept of economic crime and the conditions of responsibility. The second part is devoted to the comparison of similarities and differences with the responsibility of legal entities for criminal acts. Finally, the advantages and disadvantages of the economic offense system are pointed out.
Keywords: economic offenses; environment; crime; protection